Delimitação e cálculo de espessura de alterações antropogênicas no relevo: estudo de caso no município de São Carlos, SP - Capoia, Emilene Frazão (2021)
Human activity usually results in the modification of the landscape, particularly in an urban environment. Therefore, as the speed of these changes intensifies, remodeling the relief, the need for monitoring and analysis of these transformations emerges. The present work aimed to rescue and revitalize the cartographic documents and historical aerial images of the Jockey Clube neighborhood in the city of São Carlos-SP, Brazil, to understand the evolution of the relief through the alterations caused during the occupation of the studied area in the years of 1970, 1989, and 2011. For this purpose, the digitalization of historical maps and their georeferencing was performed. From these documents, the DEMs were generated for the calculation of the geometry of the anthropogenic deposits, enabling the comparative multitemporal analyzes within the studied period. From the proposed analyses, it was possible to trace the evolution of the relief and the changes in the direction of the surface flow, which allowed an understanding of the anthropization that occurred. The cartographic products showed differences in volumetric measures, demonstrating that, over the years, the widest range of change in relief thickness was between -1 and 1 m. In the period between 1970 and 1989, there was a decrease in the thickness of the layers of materials that make up the relief around the head of the river, indicating erosive processes. In the following periods, increases in the thickness of this same region were observed, caused by landfills aimed at mitigating the erosive process, which may have caused the headwater to retreat due to anthropogenic deposits. Another pattern perceived in the region concerns the landfills, which occurred mostly in regions that showed an increase in built-up areas. Thus, it was concluded that the adopted methodology proved to be efficient for the delimitation of the change in the relief thickness. Even though it was low-cost, it yielded satisfactory results, which allowed the observation of patterns over time.